ANALISIS SERVICE QUALITY SIAKAD TERHADAP KEPUASAN USER (Studi Kasus: Mahasiswa Prodi Akuntansi Politeknik Harapan Bersama) - Bahri Kamal; Ghea Dwi Rahmadiane; Erni Unggul Sedya Utami (Monex: Journal of Accounting Research, 2019)
User satisfaction is very important for an educational institution, one of them is a university. Quality services are absolutely necessary to meet student expectations, the better the quality of SIAKAD given by the university to students will also provide various benefits to the university. This research has several problem boundaries, among others, focusing on the analysis of five dimensions of service quality, namely tangibles, reliability, responsiveness, assurance, and empathy to user satisfaction. Respondents in this study were SIAKAD users, especially students of the Accounting Department at Polytechnic of Harapan Bersama Tegal of 2015-2017. The population of this study were students of Accounting Department of 2015-2017 in Polytechnic of Harapan Bersama Tegal totaling 1,271 students. The sampling technique used was Proportionate Stratified Random Sampling, where samples were taken based on strata. One way to determine the sample size in this study were to use the Slovin formula, amounting to 93 respondents. The method of analysis in this study used validity test, reliability test, classic assumption test, and simple linear regression test. The hypothesis in this study there was an influence between Service Quality of SIAKAD on user satisfaction. The results of this study indicate that the service quality (X) variable was obtained with tcount value were 1.301 then tcount > ttable were 1.301 > 0.677 then the hypothesis was accepted which means that the service quality (X) variable influences user satisfaction (Y). The results of Ndori, Akhmad (2015), Taman, Abdullah et al (2013), Fikri, Sirhan et al (2016), and Murgiono (2010) showed that service quality had a positive effect on student satisfaction.Keywords : service quality, user satisfaction, SIAKAD